Non-Proximity as Well as Immediate Tracking for Phosphor Heat Within Phosphor-Transmuted WLED Apparatuses - Nguyen Thi Phuong Loan; Phan Xuan Le; Phan Thi Minh Man (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
Phosphor-transmuted white illuminating diode units (ptWLEDs) prove to be an essential illumination means for universal illumination. For balancing the photometrical attributes for ptWLED apparatuses, significant endeavors are still aiming at regulating the thermic abatement for LED colorants. The thermic issues for phosphor components, being a profound dependability trouble in ptWLED apparatuses, continue to be a significant subject for research. The study herein concerns a reliable method capable of assessing phosphor heat within functioning ptWLED via a non-proximity, immediate tracking technique for distantly tracking the discharge spectrum. Usually, infrared cameras or thermocouples would be employed for assessing heat. IR cameras need decent calibrating for discharge and would be typically obstructed via lenses or disparate modules covering phosphor samples. Furthermore, thermocouples need a period for achieving thermic anology among the tracker as well as samples subject to experiment. Said method would be detrimental if employed in intrinsic tracking. The method herein offers benefits surpassing ordinary techniques for non-intrusiveness, non-proximity, immediate as well as intrinsic tracking. Said technique would not be influenced by apex wavelength for pump illumination, the dosage as well as breadth for phosphors as well as correlated chroma heat (CCT).